2011
DOI: 10.1210/en.2011-0225
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ-Independent Increase in Glucose Uptake and Adiponectin Abundance in Fat Cells

Abstract: Although thiazolidinediones (TZD) effectively improve hyperglycemia and increase adiponectin, a proinsulin-sensitizing adipokine, they also increase adipogenesis via peroxisome proliferator-activated receptor (PPAR)γ induction, which may be undesirable. Recent safety concerns about some TZD have prompted the search for next generation agents that can enhance glycemic control and adiponectin independent of PPARγ or adipogenesis. Reminiscent of TZD action, a human adenovirus, adenovirus 36 (Ad36), up-regulates P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
2
41
1
Order By: Relevance
“…Ascofuranone, which has an anti-hyperlipidemia effect, can also increase the levels of PPAR-γ and adiponectin in 3T3-L1 preadipocyte cells (31). Previous studies have revealed that GLP-1 increases insulin sensitivity by upregulating Glut-4, thus reducing macrophage infiltration, inhibiting inflammatory pathways and reducing fat mass in adipocytes (29,30). Our results suggest an alternative mechanism whereby GLP-1 increases insulin sensitivity.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Ascofuranone, which has an anti-hyperlipidemia effect, can also increase the levels of PPAR-γ and adiponectin in 3T3-L1 preadipocyte cells (31). Previous studies have revealed that GLP-1 increases insulin sensitivity by upregulating Glut-4, thus reducing macrophage infiltration, inhibiting inflammatory pathways and reducing fat mass in adipocytes (29,30). Our results suggest an alternative mechanism whereby GLP-1 increases insulin sensitivity.…”
Section: Discussionsupporting
confidence: 52%
“…It has also been reported that an increase in the number of small subcutaneous adipocytes promotes lipid metabolism and insulin sensitivity (9,(29)(30)(31). The PPAR-γ agonist TZD has been shown to stimulate preadipocyte differentiation, to increase the number of small subcutaneous adipose cells, to improve insulin sensitivity and to prevent excess lipid accumulation through the upregulation of the expression of Glu-4 and adiponectin (29,30).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Adv36 DNA in differentiated cells 95 expresses transcription factors and induce enzymes that may contribute to the development of 96 obesity by a variety of mechanisms. For example, Adv36 infection is associated with 97 increased differentiation of adipocytes and pre-adipocytes in vitro 8 , along with evidence of 98 increased glucose uptake and de novo lipogenesis 12 , and with recruitment of adipocytes from 99 adult stem cells within adipose tissue 13,14 . Therefore, Adv36 appears to induce both 100 hypertrophy and hyperplasia of fat cells.…”
Section: Introduction 70mentioning
confidence: 99%
“…Atherosclerosis, the inflammatory response, and impaired vascular endothelial function play an important role in the development of cerebral infarction (Pucci et al, 2011;Soskić et al, 2011). The fact that PPARγ mediates effects on atherosclerosis, insulin resistance, inflammation, and lipoprotein metabolism may be relevant to this disease (Gallardo-Soler et al, 2008;Dubuisson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%